Study of Hadith Living in All Islamic Boarding Schools in Medan, Indonesia - Ahmad Faisal; Ramli Abdul Wahid; Sulidar Sulidar (Budapest International Research and Critics University, 2019)
Hadith for Muslims is an important thing because in it revealed various traditions that developed during the time of the Prophet. Traditions that lived during the prophetic period refer to the person of the Prophet. as a messenger of Allah SWT. In it the conditions for various Islamic teachings, therefore, sustainability continues to run and develop until now along with human needs. The continuation of the tradition is so that humanity today can understand, record and implement guidance on Islamic teachings that are in accordance with what the Prophet Muhammad exemplified. Practices of worship carried out are sources of arguments. Therefore, Friday azan twice is a sunnah (habit) which was revived during the leadership of Caliph Usman bin Affan. Because at the time of the Prophet Muhammad. the usual Friday call to prayer is only one time. The reason why Usman did this was because of the progress of the Islamic region and the increasingly busy activities of Muslims. So to perform Friday prayers is not enough to call only once.